WATER RESOURCE SUSTAINABILITY IN THE UPPER PARANAPANEMA-SP BASIN: A SYSTEMS DYNAMICS APPROACH - Gonzalez, Alba Maria Guadalupe Orellana [UNESP]; Saad, João Carlos Cury [UNESP]; Sánchez-Román, Rodrigo Máximo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2024)
The agricultural sector is directly impacted by climate conditions. Global climate change (GCC) model projections indicate that Brazil will experience increases in temperature and variations in precipitation. In this climate change scenario, it is becoming increasingly necessary to understand the impacts that these changes will have on water resources and agriculture. Therefore, the aim of this research was to identify the probable impacts on irrigated agriculture and water resources from the perspective of different climate change scenarios in the Upper Paranapanema River Basin (BH of the ALPA), SP, by assessing their probable repercussions. The model made it possible to assess the impacts caused by climate change, manifested in changes in rainfall, on irrigated agriculture and water resources in the BH of the ALPA. The evaluation was carried out via the Falkenmark, Keller, and sustainability indices. When the business-as-usual (BaU) scenario is analyzed, the results indicate that the basin's water resource system maintains water sustainability throughout the simulation period (2016--2070).
SUSTENTABILIDADE DOS RECURSOS HÍDRICOS NA BACIA DO ALTO PARANAPANEMA-SP: UM ENFOQUE DE DINÂMICA DE SISTEMAS
Keywords: STELLA; systems thinking; water balance